Mycobacterial disease in patients with chronic granulomatous disease: A retrospective analysis of 71 cases - (:unkn) unknown (MOSBY-ELSEVIER, 2016)
Background: Chronic granulomatous disease (CGD) is a rare primary immunodeficiency caused by inborn errors of the phagocyte nicotinamide adenine dinucleotide phosphate oxidase complex. From the first year of life onward, most affected patients display multiple, severe, and recurrent infections caused by bacteria and fungi. Mycobacterial infections have also been reported in some patients. Objective: Our objective was to assess the effect of mycobacterial disease in patients with CGD. Methods: We analyzed retrospectively the clinical features of mycobacterial disease in 71 patients with CGD. Tuberculosis and BCG disease were diagnosed on the basis of microbiological, pathological, and/or clinical criteria. Results: Thirty-one (44%) patients had tuberculosis, and 53 (75%) presented with adverse effects of BCG vaccination; 13 (18%) had both tuberculosis and BCG infections. None of these patients displayed clinical disease caused by environmental mycobacteria, Mycobacterium leprae, or Mycobacterium ulcerans. Most patients (76%) also had other pyogenic and fungal infections, but 24% presented solely with mycobacterial disease. Most patients presented a single localized episode of mycobacterial disease (37%), but recurrence (18%), disseminated disease (27%), and even death (18%) were also observed. One common feature in these patients was an early age at presentation for BCG disease. Mycobacterial disease was the first clinical manifestation of CGD in 60% of these patients. Conclusion: Mycobacterial disease is relatively common in patients with CGD living in countries in which tuberculosis is endemic, BCG vaccine is mandatory, or both. Adverse reactions to BCG and severe forms of tuberculosis should lead to a suspicion of CGD. BCG vaccine is contraindicated in patients with CGD.
Keywords: Mycobacteria; BCG; chronic granulomatous disease; tuberculosis; primary immunodeficiency; CLINICAL-FEATURES; 1ST REPORT; 2 CHILDREN; TUBERCULOSIS; MUTATIONS; INFECTIONS; SUSCEPTIBILITY; VACCINATION; OXIDASE; REGION